Penyusunan Laporan Keuangan Berdasarkan SAK EMKM dan Pelaporan Pajak pada Langgeng Bakery 99 Kabupaten Magetan - hedi pandowo (Universitas Merdeka Madiun, 2020)
Abstract— The purpose of this research is to assist Langgeng Bakery 99 in preparing financial statements for 2018 and 2019 in accordance with the Financial Accounting Standards for Micro, Small and Medium Enterprises (SAK EMKM) intended as a reference in preparing financial statements for MSMEs and provide information about filling the Annual Tax Return. The preparation of financial statements based on SAK EMKM will present three financial statements, namely the income statement, statement of financial position, and notes to the financial statements. Source of data used in this research are primary data and secondary data. The type of data used is quantitative data and qualitative data. Data collection is done by interview, observation, documentation study, and data triangulation. The results of this research are financial statements based on SAK EMKM, including: comparative income statement which shows the net profit after tax of Langgeng Bakery 99 in 2018 is Rp220,471,627 and in 2019 is Rp306,977,942, a comparative statement of financial position that presents total assets in 2018 and total liabilities and equity equal to Rp1,270,885,794 and for 2019 of Rp1,493,196,958, as well as notes to the financial statements and annual tax return of Langgeng Bakery 99 tax year 2019. The researcher suggests that Langgeng Bakery 99 will continue to compile financial statements based on SAK EMKM in accordance with what has been made by researchers to make it easier for companies in tax reporting and business development. Keywords—: UMKM, Financial Statement, SAK EMKM, Annual Personal Income Taxpayers Tax Return (Form 1770).